REKAYASA WEB DENGAN W2000 - Ronaldo, Deddy (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2014)
Information Technology Journal is published by means of print, the Journal used to facilitatethe research conducted lecturers Information Engineering and mutually assess each study, theassessment can be used to take care of faculty rank. Web engineering methods using W2000, whichuse a model object-oriented modeling is the Unified Modeling Language (UML). Journal ofTechnology website is expected to help the dissemination of research lecturers InformationEngineering Palangkaraya University and in addition there will be a feature to be able to assessReviewers and print documents directly in the assessment website